Bioremediation of Chromium [Cr (VI)] In Tannery Effluent Using Bacillus spp and Staphylococcus spp - Mythili, K (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTChromium is the most toxic and common among the heavy metal pollutants of industrial effluents. In the present study, biosorption of Chromium by microorganisms from tannery effluent was investigated. The efficient bacteria isolated from tannery effluent were identified as Bacillus spp and Staphylococcus spp. The effect of pH and temperature on the biosorption capacity was investigated. From the optimization study the effective pH 7 and temperature 35?é??C was maintained in tannery effluent for Bacillus spp and Staphylococcus spp. The chromium content of the effluent was around 140 mg/L before remediation, after that the metal removal percentage was 86 and 74. The best activity was observed by Bacillus spp followed by Staphylococcus spp. Key words: Bioremediation, Cr (VI) reduction, Chromate-resistant bacteria